The Role of Independent and Alternative Media in Conducting Investigative Journalism - Atay, Sh. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2025)
This article examines the role of independent and alternative media in conducting journalistic investigations, focusing on the coverage of the protests that occurred in Kazakhstan in January 2022. The study presents a comparative analysis of materials published on three online platforms: «Azattyq», «Vlast» and «Inbusiness». The research employs content analysis and case study methods to identify the specific features of coverage, as well as to determine the methods and approaches used by each of these sources. The analysis focuses on articles published on 5 and 6 January 2022, which address the protests and the authorities’ response to them. The findings reveal that the «Azattyq» and «Vlast» websites actively engage in journalistic investigations, incorporating the viewpoints of protest participants, experts, and detailed accounts of the unfolding events. In contrast, the «Inbusiness» website predominantly focuses on the official government response, reporting on the measures taken to suppress the protests and restore order, while the materials lack in-depth analysis of the events and opinions from opposition experts. In conclusion, recommendations are provided for improving journalistic investigation practices, expanding the representation of independent viewpoints in materials, and enhancing the level of objectivity in the coverage of significant events.